Chitosan oligosaccharides maintained postharvest quality and increased shelf life of mango - Nishat Nitu; Md. Sefat Ullah; Prianka Howlader; Md. Nazmul Mehedi; Habiba Meem; Santosh Bose (Journal of Horticulture and Postharvest Research, 2025)
Purpose: Mango is one of the most important and widely cultivated climacteric fruit which ripens rapidly after harvesting. It exhibits very short shelf life mainly due to high respiration rate, susceptible to various storage pathogens and mechanical injuries at the time of postharvest management which lead to reduce the quality. However, the experiment was carried out to investigate the chitosan oligosaccharides (COS) coating effects on postharvest quality and shelf life of mango varieties. Research Method: Mango fruits of two selected varieties (Langra and Amropali) were collected at mature stage. Changes in different physico-chemical characteristics were studied at different days of storage under ordinary room condition through different COS concentration viz., control, COS 25 mg/L, COS 50 mg/L, COS 100 mg/L, COS 250 mg/L and COS 500 mg/L. The two factor-experiments were laid out in a completely randomized design with three replications. Findings: Results demonstrated that COS had a positive effect on retaining higher amount of anthocyanin content, total sugar and total soluble solid content. Moreover, COS treated fruits exhibited significant delays of firmness, weight loss percentage, titratable acidity, pH and vitamin C content compared to untreated fruits. In addition, between two varieties of mango, Langra exhibited better performance compared to Amropali when treated with COS 100 mg/L. Research Limitations: The study did not focus on ethylene biosynthesis and respiration rate determination. Originality/Value: COS 100mg/L have great potentiality to maintain postharvest quality and increase shelf life of mango which could be applied commercially for preservation of mango in an ecofriendly manner.